Meaning in life measure: a five-Item short form and its measurement invariance across gender, age, and cultural contexts. (3rd April 2023) - Li, Xu; Sim, Wonjin; Hill, Clara E.
Abstract: Objective: The aims of this study were to develop a revised version of the Meaning In Life Measure (MILM; Hill et al., 2019) and investigate its multilevel measurement invariance at the between-person and within-person levels and multi-group measurement invariance across gender, age, and cultural groups. Methods: We analyzed an international dataset including data from 1600 sessions with 384 clients in five continents (Africa, Asia, Europe, Latin America, and North America) using multilevel item response theory and multilevel factor analysis. Results: We found that the revised 5-item MILM-5 had satisfactory reliability and structural validity with the overall sample. Further, it demonstrated measurement invariance across the between- and within-person levels, and also across gender and age groups. Across representative countries within continents, the MILM-5 had the same overall factor structure but all factor loadings and item intercepts significantly differed across cultural contexts. Implications are discussed regarding the assessment of meaning in life in international clinical settings.